2003
DOI: 10.1083/jcb.200305006
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of integrin α6β4 signaling in lipid rafts

Abstract: Integrin α6β4 signaling proceeds through Src family kinase (SFK)–mediated phosphorylation of the cytoplasmic tail of β4, recruitment of Shc, and activation of Ras and phosphoinositide-3 kinase. Upon cessation of signaling, α6β4 mediates assembly of hemidesmosomes. Here, we report that part of α6β4 is incorporated in lipid rafts. Metabolic labeling in combination with mutagenesis indicates that one or more cysteine in the membrane-proximal segment of β4 tail is palmitoylated. Mutation of these cysteines suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(126 citation statements)
references
References 28 publications
5
120
1
Order By: Relevance
“…Therefore, it is possible that curcumin may affect one of the signaling pathways responsible for the phosphorylation of these Ser residues. Alternatively, palmitoylation of membrane proximal Cys residues of b4 integrin is required for lipid raft localization of a6b4 (20). On the basis of our data, which show that curcumin shifts a6b4 from lipid raft to nonlipid raft fractions (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it is possible that curcumin may affect one of the signaling pathways responsible for the phosphorylation of these Ser residues. Alternatively, palmitoylation of membrane proximal Cys residues of b4 integrin is required for lipid raft localization of a6b4 (20). On the basis of our data, which show that curcumin shifts a6b4 from lipid raft to nonlipid raft fractions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mobilization of a6b4 from HDs to leading edges of migrating carcinoma cells is thought to increase the localization of a6b4 into lipid rafts (16), where lots of other signaling receptors are located in the near vicinity so that a6b4 acts as a signal amplifier of these receptors (20,21,31). Therefore, we tested whether curcuminmediated a6b4 sequestration in HDs affects localization of a6b4 in lipid rafts (Fig.…”
Section: Curcumin Prevents Localization Of A6b4/egfr To Lipid Raftsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, galectin-3 might play an important role in the ternary complex formation in lipid rafts. Compartmentalization of lipid rafts is necessary to couple ␣6␤4 integrin and EGFR to active Src family kinase, which both prevents incorporation of ␣6␤4 integrin into hemidesmosomes and promotes cell migration (42,44,57). Some studies have reported that integrins are localized in the so-called glycosphingolipid-enriched microdomain rather than existing in lipid rafts on the cell surface.…”
Section: Discussionmentioning
confidence: 99%